When video production moves into the Mathematics classroom (Revista BOEM, 2024)
How do public school students express mathematical content through digital video? This question promoted reflections on the production ‘Complex Numbers’, prepared by high school students, which we analyzed in light of multimodality, in addition to conducting the investigation based on a qualitative approach. To this end, we narrate the wanderings of a public school character we call Chico, we highlight some of his memories and we list excerpts from Pitty’s music. The data suggest that carrying out the activity is associated with an experience ‘totally different from the common classroom’, something ‘interesting’ for the students, which required attention, organization, creativity, and spontaneity. In our understanding, the demonstrations of these students announce that the engagement with the video production activity enabled learning, the deepening of themes, the meeting of groups, as well as the recognition that digital technology brings people together and plays ‘a role extremely important’ in education networks.
Keywords: digital technology; video production; multimodality